Impact of the organic bedding type on the productive and reproductive performance of Holstein cows housed in free stall (Research, Society and Development, 2020)
Organic beds are being used in free stall for the purpose of later use for fertilization. The objective was to evaluate the productive and reproductive performance of Holstein cows in two bed groups: eucalyptus wood shavings (ME) and crushed corn cobs (SMT). For 180 days, data on clinical mastitis and daily milk production were collected. Monthly, during the experimental period, virgin and present in the beds samples of ME and SMT were collected to determine bacterial growth and milk samples from each cow for electronic analysis of somatic cell count (CCS). Quantitative data were submitted to the Tukey test and qualitative data to the Chi-square test. Cows housed in SMT showed higher CCS in the third month of lactation and higher milk production at 180 days of lactation than cows in ME. There was no difference in peak lactation days, peak milk production, number of clinical mastitis cases, conception rate and pregnancy loss between the groups evaluated. It is concluded that eucalyptus shavings and crushed corn cobs showed satisfactory results to be used as organic bed, as they presented low somatic cell count, did not interfere in the number of cases of clinical mastitis and in the conception rate at the first artificial insemination.